Broadband optical absorption of amorphous carbon/Ag nanocomposite films and its potential for solar harvesting applications - Zoubos, H.; Koutsokeras, Loukas E.; Anagnostopoulos, Dimitrios F.; Lidorikis, Elefterios; Kalogirou, Soteris A.; Wildes, Andrew R.; Kelires, Pantelis C.; Patsalas, Panos A. (My University, 2013)
The emergence of Localized Surface Plasmon Resonance (LSPR) in nanocomposite films consisting of a hydrogen-free amorphous Carbon (a-C) matrix and Ag is considered theoretically and experimentally. While in theory it could be manifested for highly tetrahedral (>90% sp3) matrices, Auger electron spectroscopy and neutron reflectivity have shown that the incorporation of Ag into the a-C matrix induces severe graphitization that eliminates the LSPR; nonetheless, the dielectric damping of graphitized a-C, in combination with the π-π* electronic transitions of carbon and the defect states introduced by Ag, cumulatively result in a strong broadband optical absorption in the near infrared, visible and UVA/UVB spectral ranges, revealed by optical reflectivity spectra, that coincides with the solar emission spectrum. The incorporation of Ag into a-C at room temperature thus proves to be an energy-efficient pathway for the controlled graphitization and the tailored optical absorption of novel nanocomposite films for solar photothermal applications.
Keywords: Amorphous carbon; Effective medium approximation; Nanocomposites; Plasmonics; Solar absorption